Analisis Online Customer Review Terhadap Kepercayaan Konsumen Dan Keputusan Pembelian (Studi Kasus Pada UMKM Iroh foods): (Case Study on MSME IROH Foods) - Lukitasari, Lenni; Tiara, Hana (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2024)
Online shopping has become a common phenomenon in modern society, influencing consumer purchasing behavior. This study aims to analyze the relationship between online customer reviews and consumer trust, thereby influencing purchasing decisions. Iroh Foods, which sells frozen risoles products through the Instagram platform and website, and conducts transactions via WhatsApp. This research uses a qualitative approach and the types of research used are descriptive qualitative methods. By involving Iroh Foods owners and consumers as sources in data collection. Data collection techniques are conducted using interviews, observation, and documentation. Samples are taken using purposive sampling techniques by interviewing 9 people consisting of owners and also consumerS. The results showed that online customer reviews have a significant effect on consumer trust and influence purchasing decisions at Iroh Foods. Positive reviews help to increase consumer confidence, while negative reviews help consumers consider product risks. Responsiveness to reviews and criticism are important factors in building consumer trust. Online customer reviews play a crucial role in shaping consumer trust and influencing purchasing decisions.